Evaluation Program of Garbage Bank as Development Efforts of Society on Garbage Management in Jepara, Central Java - Anita Dyah Asmaranti (Jurnal Daulat Hukum, 2018)
This study entitled: "Evaluation Of Garbage Bank As Development Effort of Society On Garbage Management In Jepara, Central Java". This study intends to evaluate the implementation of the Garbage Bank program and find out how the community participation and the obstacles in implementing the Garbage Bank program. This study uses qualitative research design methods and approaches Inductive Descriptif. Informants consisted of elements: Local Government, Community and Garbage Bank managers in each group. For the purposes of data analysis, the author uses the theory of evaluation with CIPP evaluation method whereby elements analyzed consisted of: content, Input, Process and Product and normative rules related to the object and the subject studied. Based on the results of data processing and analysis we concluded that the Garbage Bank implemented in Jepara has been running quite well but is still in the stage of education in which the targets are achieved is to introduce the public to the program so that the program later to become a forum for community empowerment. Community participation has been good enough, but of course there are still many shortcomings that need to be improved, among other things: lack of infrastructure, limited human resources, lack of socialization, limited funds and limited garbage recycling product market. The solution is, of assistance to the Garbage Bank community, training and socialization, open markets products through exhibitions.Keywords: Evaluation; Empowerment; Garbage Bank.